Mechanical Mixture (MM) Materials for Cyclic CO₂ Power-to- Methane: Filler Influence and Stability - Mercader Plou, Víctor Daniel; Glaser, Jonas; Durán, Paúl; Sanz Monreal, Pablo; Aragüés Aldea, Pablo; Francés, Eva; Herguido, Javier; Peña Llorente, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2025)
This work explores the influence of active fillers (zeolites and alumina) in mechanical mixtures (MM) for cyclic CO₂ methanation using Ni-Fe based catalysts. Zeolites promote in situ water removal, enhancing CH₄ yield. The effect on temperature distribution and system stability was evaluated in a fixed-bed reactor under cyclic conditions.